The sociology of objects : rediscovering the importance of objects in organizational life - Downs, Alexis; Hagemeijer, Rouven (Journal of organizational change management, 2004)
Objects are produced within, and simultaneously affect, the process of organizing as a consequence of their interaction within social collectives. This paper discusses the impact and influences of the growth of post-social relations, between human and technological objects, on social and organisational arrangements. The paper presents a discussion largely at the conceptual level and draws from a variety of literatures, including the burgeoning sociology of science literature. The discussion in this paper is based on a view that posits the growth of intimate links with epistemic objects within.